UPAYA GURU DALAM MENINGKATKAN MINAT MEMBACA DAN MENULIS SISWA SDN PULAU RIMAU KABUPATEN BANYUASIN - Ruslan, Ruslan; Wibayanti, Sri Hayu (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to determine the efforts of teachers in increasing interest in reading and writing at Pulau Rimau Elementary School in Banyuasin Regency. The results of this study are expected to increase students' insight in increasing motivation to read and write. In addition, writing skills can stimulate students to think and reason more critically, and their courage to be active and interactive during the teaching and learning process, (2) for Indonesian language instructors. The results of this study are expected to contribute to teaching Indonesian at elementary school level to obtain knowledge and information about the motivation to read and write students so that teachers can improve the quality of education and teaching Indonesian language, especially reading and writing. The results of the research, findings and discussion of the teacher in increasing interest in reading and writing students at Pulau Rimau Elementary School Banyuasin Regency were obtained from the results of interviews and observations were analyzed using qualitative descriptive analysis techniques, and some material from the informants. Based on the results of the study, it can be concluded: The efforts of Indonesian language teachers in increasing interest in reading and writing students at Pulau Rimau Elementary School Banyuasin Regency have been running quite well from planning to the implementation process in the classroom.